AKUNTANSI ZAKAT: KAJIAN PSAK 109 (Studi Kasus Pada BAZNAS Kota Makassar) - Lince Bulutoding; Wiwi Anggeriani (Universitas Islam Balitar, 2018)
This study aims to analyze the management of zakat in BAZNAS Kota Makassar on implementing Zakah Accounting based on PSAK 109. This is a qualitative research with case study. The data collection technique done through interview. The results showed that Badan Amil Zakat Nasional (BAZNAS) Makassar City has performed its duties and functions as the Amil Zakat Agency in accordance with Law No.23 Year 2011. However, the financial statements that have been compiled are not in accordance with the standard contained in PSAK 109 on Accounting for Zakah.